Naturally Nourished Kids: The Whole-Food Approach for Balanced Minds and Bodies at Every Developmental Stage - Miller, Ali, (Dietitian); Yoo, Becki (Beverly, MA, USA : Fair Winds Press, an imprint of The Quarto Group, 2025)
"In Naturally Nourished Kids, beloved real food mamas and leading Functional Medicine dietitians Ali Miller and Becki Yoo present 100 low-glycemic, anti-inflammatory real-food recipes for kids from toddler to teenager"-- Provided by publisher.
Includes index.
new book 2025 fall.
Keywords: Low-carbohydrate diet -- Recipes; Glycemic index; Inflammatory bowel diseases -- Diet therapy; Cookbooks; School children -- Food; Cooking for Kids; Cookbooks